2013
DOI: 10.1098/rsbl.2013.0592
|View full text |Cite
|
Sign up to set email alerts
|

Plastic proteans: reduced predictability in the face of predation risk in hermit crabs

Abstract: Variation in behaviour occurs at multiple levels, including between individuals (personality) and between situations ( plasticity). Behaviour also varies within individuals, and intra-individual variation (IIV) in behaviour describes within-individual residual variance in behaviour that remains after the effects of obvious external and internal influences on behaviour have been accounted for. IIV thus describes how predictable an individual's behaviour is. Differences in predictability, between individuals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
135
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(154 citation statements)
references
References 17 publications
13
135
6
Order By: Relevance
“…We also found, similar to previous studies, that crab mass had no effect on the mean duration of startle responses [44]. Although we have controlled for mass in previous analyses of IIV [3,8,9], this is the first time that we have tested the 46], the size range of crabs used in this study represents only a small proportion of the size and hence age range of sexually mature males. Thus, ontogenetic variation is unlikely to underpin this trend for increasing unpredictability with crab mass.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We also found, similar to previous studies, that crab mass had no effect on the mean duration of startle responses [44]. Although we have controlled for mass in previous analyses of IIV [3,8,9], this is the first time that we have tested the 46], the size range of crabs used in this study represents only a small proportion of the size and hence age range of sexually mature males. Thus, ontogenetic variation is unlikely to underpin this trend for increasing unpredictability with crab mass.…”
Section: Discussionsupporting
confidence: 84%
“…Long startle responses reduce the time available for other activities, but provide a mechanism for avoiding risk. Thus, in hermit crabs, startle responses increase in duration under conditions of high risk [9,44,51]. Similar positive associations between risk level and hiding time are also seen in other species (e.g.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Individual personality also can contribute to how animals respond to risk (Sih et al 2015), and variation across individuals might result from high individual repeatability in behaviours over time (Carrete and Tella 2010, 2013Briffa 2013;Highcock and Carter 2014). Within-individual variability reflects the predictability or repeatability of an animal's behaviour (Briffa 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within-individual variability reflects the predictability or repeatability of an animal's behaviour (Briffa 2013). For example, Carrete and Tella (2010) found that breeding Burrowing Owls (Athene cunicularia (Molina, 1782)) exhibited relatively high repeatability (0.84-0.92; low within-individual variation) in flight initiation distance (FID) in response to human approaches toward burrows, and speculated that selection and distribution of breeding sites reflected different levels of individual tolerance to human disturbance.…”
Section: Introductionmentioning
confidence: 99%